Leveraging IoT and GPS for Real-Time Supply Chain Monitoring and decision-making during Assembly and Test Processes - Srinivas Vikram (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Real-time orchestration of assembly-and-test (A&T) flows is still hamstrung by blind spots between in-plant operations and in-transit logistics. We present an Internet-of-Things (IoT) and Global Positioning System (GPS) convergence stack that streams machine telemetry and geo-spatial events into a low latency edge-to-cloud analytics pipeline. The architecture—built on MQTT 3.1.1, CoAP/UDP, and Apache Flink—delivers sub-2 s event-to-action latency while processing 18 k msg s−1 across 74 edge nodes. In a six-month deployment at a mid-volume electronics manufacturer, the system cut average A&T dwell time by 37 %, reduced expedite shipments by 28 %, and improved decision accuracy to 92.3 % versus a rules-only baseline. A threat analysis details TLS/DTLS-secured links and role-based access controls; cost modelling shows payback in 11 months on a 220 k CAPEX. Limitations—GPS occlusion, sensor drift, protocol heterogeneity—are discussed alongside future work on ultrawideband indoor positioning and digital-twin what-if simulation. Results confirm that tightly coupled IoT–GPS visibility materially boosts responsiveness, throughput, and cost efficiency in A&T centric supply chains.